Avaliação da atividade anti-inflamatória e antinociceptiva do extrato hidroalcoólico de Eugenia punicifolia (Kunth) DC - Basting, Rosanna Tarkany [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Inflammation is an immune complex-related tissue damage and / or cell caused by chemical, physical, immunological or microbial. The inflammatory process involves a complex cascade of biochemical and cellular events, including awareness and receptor activation, lysis and tissue repair. In general, tissue damage trigger a local inflammatory response by recruiting leukocytes, which release inflammatory mediators. These substances are able to sensitize nociceptors. After synaptic transmission and signal modulation by nociceptive sensory neurons, these signals are perceived as pain. Pain is an experience that involves multiple factors. The route of the supraspinal pain control originates in many brain regions, such as substance periarquedutal gray (PAG), median raphe nucleus and rostral ventromedial medulla (RVM) and have a critical role in determining the chronic and acute pain. Anti-inflammatory drugs (NSAIDs) are used to control inflammation, which inhibit the inflammatory mediators, but can cause side effects such as stomach ulcers and cardiovascular damage. An alternative for the treatment of pain and inflammation is the use of plant species. The genus Eugenia belongs to the family Myrtaceae, one of the largest botanical families of expression in the Brazilian ecosystems. From the pharmacological point of view, studies of similar species crude extracts showed the presence of anti-inflammatory, analgesic, antifungal, hypotensive, antidiabetic and antioxidant activity of some species. As a class of importance in therapeutic phytochemical, the flavonoids has represented an important group with significant anti-inflammatory and gastroprotective, and are present in a significant way in the chemical composition of genus Eugenia. The project´s overall objective is to evaluate the antinociceptive and anti-inflammatory activities from hydroalcoholic extract of leaves of Eugenia punicifolia (EHEP). In this work we performed acute toxicity ...

A inflamação é uma resposta imune complexa relacionada ao dano tecidual e/ou celular causada por estímulos químicos, físicos, imunológicos ou microbianos. O processo inflamatório envolve uma complexa cascata de eventos bioquímicos e celulares, que inclui sensibilização e ativação de receptores, lise e reparo tecidual. Em geral, as lesões teciduais desencadeiam uma reação inflamatória local recrutando leucócitos, que liberam mediadores inflamatórios. Essas substâncias são capazes de sensibilizar nociceptores. Após a transmissão sináptica e modulação do sinal nociceptivo pelos neurônios sensoriais, esses sinais são percebidos como “dor”. A dor é uma experiência que envolve múltiplos fatores. A via supraespinal do controle da dor se origina em muitas regiões cerebrais, tais como substância periarquedutal cinzenta (PAG), núcleos medianos da rafe e medula rostral ventromedial (RVM) e possuem papel crítico na determinação da dor aguda e crônica. Os medicamentos Anti-inflamatórios Não Esteroidais (AINEs) são utilizados no controle da inflamação, os quais inibem os mediadores inflamatórios, mas podem provocar efeitos adversos como úlceras gástricas e danos cardiovasculares. Uma alternativa para o tratamento da dor e inflamação é a utilização de espécies vegetais. O gênero Eugenia pertence à família Myrtaceae e é uma das famílias botânicas de maior expressão nos ecossistemas brasileiros. Sob o ponto de vista farmacológico, estudos realizados com extratos brutos de espécies congêneres demonstraram a presença de propriedade anti-inflamatória, analgésica, antifúngica, hipotensiva, antidiabética e antioxidante de algumas das espécies. Como classe fitoquímica de importância na terapêutica, os flavonóides tem representado um importante grupo com relevante ação anti-inflamatória e gastroprotetora, e estão presentes de forma expressiva na composição ...
Keywords: Dor - Tratamento; Resposta imune; Agentes anti-inflamatorios; Mirtacea - Uso terapêutico; Matéria médica vegetal; Pain